The syntax of agreement and concord - Baker, Mark C. (Cambridge University Press, 2008)
'Agreement' is the grammatical phenomenon in which the form of one item, such as the noun 'horses', forces a second item in the sentence, such as the verb 'gallop', to appear in a particular form, i.e. 'gallop' must agree with 'horses' in number. Even though agreement phenomena are some of the most familiar and well-studied aspects of grammar, there are certain basic questions that have rarely been asked, let alone answered. This book develops a theory of the agreement processes found in language, and considers why verbs agree with subjects in person, adjectives agree in number and gender but not person, and nouns do not agree at all. Explaining these differences leads to a theory that can be applied to all parts of speech and to all languages
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Grammatik; Grammar, Comparative and general / Agreement; Syntaktische Kongruenz